SOCIAL ADAPTATION AS A PSYCHOLOGICAL PROBLEM (TAMADDUN NURI JURNALI, 2024)
Adaptation is a process of interaction betweyen a subject and an object, as a result of which changes occur in two interacting parts. Changes are associated with the appearance of new features, new combinations of features, selective loss or complete loss of a part of features. As a result, many authors describe adaptation through translation as adaptation of the organism to environmental conditions.